Problem Solving Ability: Strategy Analysis of Working Backwards Based on Polya Steps for Middle School Students YALC Pasuruan - Fauza, M Ruskhan; Inganah, Siti; Darmayanti, Rani; Maryanto, Bhaskoro Prasetyo Adi; Lony, Adrina (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
The purpose of this study was to analyze students' mathematics problem-solving abilities based on Polya's procedure. This may improve the math problem-solving abilities of Class VIII SMP YALC Pasuruan students. Research data were obtained from the analysis of student answer sheets, observation sheets, and student activity sheets based on indicators of problem-solving ability. This type of study has a quasi-experimental design with a pre-test and post-test design. A t-test was performed to check for improvements in each aspect of student problem-solving skills and all aspects of math problem-solving skills. The main finding of this study is that students' problem-solving ability in mathematics based on Polya's procedure outperforms students' problem-solving ability with regular learning